Offensive and defensive play in handball in a 2-year World Championship cycle: Characteristics and tendencies - Gryko, K.; Bodasinski, S.; Bodasinska, A.; Zielinski, J. (Polish Journal of Sport and Tourism, 2018)
Introduction. The analysis of players` performance with respect to technical-tactical actions is becoming a key factor influencing the focus of training programmes and the contents of training units. It also provides important information which can be used to improve players` efficiency during the game. The aim of the current study was to analyse the efficiency of technicaltactical offensive actions in positional attack as well as defensive actions performed by handball players participating in two consecutive World Men`s Handball Championships, held in Spain in 2013 and in Qatar in 2015. Material and methods. The material subjected to analysis was data describing the technical-tactical actions performed during the World Championships in Spain in 2013 and in Qatar in 2015. We analysed offensive and defensive actions, including with regard to the continent the teams represented. We performed an analysis of the documents available on the IHF website. The significance of the differences found was verified using analysis of variance (ANOVA and MANOVA). Results. The study found a significantly lower number of offensive actions in positional attack (-7.5%) and turnovers (-26.4%), higher overall efficiency (+7.2%), as well as higher efficiency of 6-m shots (+9.5%), wing shots (+7.3%), and breakthrough shots (+11.4%) at the World Championship in Qatar compared to tournament in Spain. When it comes to defensive actions, there was a significantly higher number of 2-minute suspensions (+27.5%), with a simultaneous significant reduction in the number of steals (-55.7%) and shots defended (-13.3%). Conclusions. During a two-year cycle, there was a change in the concept of playing in positional attack. In 2015, there was a significantly greater number of actions leading to a shot in the region of the opponent`s goal area as well as a higher level of activity and more aggressive play on the part of defensive players. In addition, European teams had gained an advantage over teams from other continents in terms of the efficiency of the technical-tactical actions undertaken.